Molecular and Cellular Response to Experimental Anisakis pegreffii (Nematoda, Anisakidae) Third-Stage Larval Infection in Rats - Bušelić, Ivana; Trumbić, Željka; Hrabar, Jerko; Vrbatović, Anamarija; Bočina, Ivana; Mladineo, Ivona (Frontiers in Immunology, 2018)
Background: Anisakiasis is a zoonotic disease caused by accidental ingestion of live Anisakis spp. third-stage larvae present in raw or undercooked seafood. Symptoms of this emerging infectious disease include mild-to-severe abdominal pain, nausea, and diarrhea. Some patients experience significant allergic reactions. Aims: In order to better understand the onset of anisakiasis, we aimed to: (i) histopathologically describe severe inflammatory/hemorrhagic infection site lesions in Sprague-Dawley rats experimentally infected with Anisakis pegreffii larvae; and (ii) qualitatively and quantitatively characterize the transcriptomes of affected tissues using RNA-Seq. Methodology: The experiment was performed on 35 male rats, sacrificed at 5 time points (6, 10, 18, 24 and 32 h post-infection). Gastric intubation was performed with 10 A. pegreffii larvae (N = 5 infected rats per time point) or 1.5 ml of saline (external control N = 2 rats). 16 pools, seven for muscle tissues and nine for stomach tissues, were created to obtain robust samples for estimation of gene expression changes depicting common signatures of affected versus unaffected tissues. Illumina NextSeq 500 was used for paired-end sequencing, while EdgeR was used for count data and differential expression analyses. Results: In total, there were 1372 (855 up and 517 down) differentially expressed (DE) genes in the Anisakis-infected rat stomach tissues, and 1633 (1230 up and 403 down) DE genes in the muscle tissues. Elicited strong local proinflammatory reaction seems to favor the activation of the interleukin 17 signaling pathway and the development of the T helper 17-type response. The number of DE ribosomal genes in the Anisakis-infected stomach tissue suggests that A. pegreffii larvae might induce ribosomal stress in the early infection stage. However, the downstream pathways and post-infection responses require further study. Histopathology revealed severe inflammatory/hemorrhagic lesions caused by Anisakis infection in the rat stomach and muscle tissues in the first 32 hours. The lesion sites showed infiltration by polymorphonuclear leukocytes (predominantly neutrophils and occasional eosinophils), and to a lesser extent, macrophages. Conclusion: Understanding the cellular and molecular mechanisms underlying host responses to Anisakis infection is important to elucidate many aspects of the onset of anisakiasis, a disease of growing public health concern.